1956
DOI: 10.1002/j.2050-0416.1956.tb02894.x
|View full text |Cite
|
Sign up to set email alerts
|

ENZYMIC DEGRADATION OF CEREAL HEMICELLULOSES. I. OBSERVATIONS ON THE Β-Glugosanase SYSTEM AND ITS DEVELOPMENT DURING MALTING

Abstract: An initial linear relationship between increases in reciprocal specific viscosity and in reducing group liberation has been confirmed for that aspect of /?-glucosanase activity which involves attack on /3-glucosan only at points remote from the ends of molecules, i.e., endo-/?-glucosanase activity; excess reducing groups over and above those calculated from this relation are ascribed to exo-/?-glucosanase and cellobiase, Prolonged endo-action gives progressive degradation of large molecules with ulti mate prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1958
1958
1980
1980

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The enzyme causing cytoclastic attack on j8-glucan is called endo-/?-glucanase (Preece, Aitken and Dick, 1954) and, in addition to producing large fission products, it yields on prolonged action cellobiose, laminaribiose and a series of more complex saccharides (Preece and Hoggan, 1956;Preece and Garg, i960 and Preece, Garg and Hoggan, i960).…”
Section: Preparation Of F$-glucan Preece and Mac-mentioning
confidence: 98%
“…The enzyme causing cytoclastic attack on j8-glucan is called endo-/?-glucanase (Preece, Aitken and Dick, 1954) and, in addition to producing large fission products, it yields on prolonged action cellobiose, laminaribiose and a series of more complex saccharides (Preece and Hoggan, 1956;Preece and Garg, i960 and Preece, Garg and Hoggan, i960).…”
Section: Preparation Of F$-glucan Preece and Mac-mentioning
confidence: 98%
“…Previously, Preece and Hoggan (1956), Bourne and Pierce (1970) and Bendelow (1971) have demonstrated the development of endo-B-glucanase (barley-B-glucan endohydrolase) activity in one or more barley cultivars during germination. Bass et al (1957) also reported large differences in this activity in barley and in green malt indicating that a large increase occurred during germination.…”
mentioning
confidence: 99%
“…65, 1980 vironment. Mercury was without apparent effect on endoglucanolytic activity and a lack of sensitivity to sulfhydryl-specific reagents has been noted for other endoglucanases (19,20,28). We have examined endoglucanases from Bacillus, Rhizopus, and Phaseolus cell wall preparations and none display sensitivit7, in terms of altered activity or specificity, toward 100 uM Hg + (Huber, unpublished).…”
Section: Resultsmentioning
confidence: 92%
“…Concentrations exceeding 3 M, however, do not significantly increase activity yields nor further reduce cell wall protein levels (Huber, unpublished (14,28,34,36), and the lack of complete inhibition observed in some instances might be explained on the basis of the inhibitor employed (i.e. HgCl2 versus pCMB).…”
Section: Resultsmentioning
confidence: 99%